Operation of the Mardoc Application in the Operational Section of the Ship Certificate Service - Evada Rustina; Sri Sayekti Lestari; Dorma Ceria Purba; Ufik Deriantoro; Endriyatno Sulastomo (International Journal of Economics, Business and Innovation Research, 2023)
MARDOC application is software owned by PT. Pelindo Marine Service which is also referred to as Marine Document. The purpose of this study is to find out how the MARDOC application operates and find out the function of the MARDOC application for companies. The method used in this study is a qualitative descriptive research method. Data collection techniques use observation and documentation methods. The results of the study stated that in the operation of the MARDOC application, service users must know the username and password to access the service as needed. The MARDOC application, especially for companies, is to facilitate service and data storage for company operational activities.